Análise da estabilidade aeroelástica de painéis sanduíches viscoelásticos em regime subsônico empregando o método doublet-lattice não planar. - Cunha, Bruno Sousa Carneiro da (2022)
The engineers of aeronautical industries are frequently facing with subsonic panel flutter phenomena, where the design and analyses of aerospace vehicles requires the knowledge of their critical flutter speeds for safety requirements and to avoid catastrophes. Thus, whenever possible it is important to evaluate efficient and low cost aeroelastic control strategies to deal with the problem of panel flutter phenomenon. In this context, the use of passive constraining viscoelastic layers seems to be an interesting alternative to be used in such situations. However, the structural and aerodynamic modeling procedures of an aeroviscoelastic system subjected to a subsonic airflow are not easy. In most of the cases, the difficult is related to the fact that, the viscoelastic behavior depends strongly on the excitation frequency and temperature, resulting in some difficulties during the coupling between the structural and aerodynamic models to account for the unsteady aerodynamics and complex behavior of the viscoelastic part, simultaneously. In this study, it is proposed an efficient numerical strategy to model aeroviscoelastic systems under subsonic airflows for panel flutter suppression. Here, the curved panel model of a thin three-layer sandwich panel and aerodynamic loadings using the nonplanar Doublet-Lattice method (DLM) are constructed both in MATLAB® environment code denominated AEROSOLVER that is interfacing the commercial software ANSYS® that is responsible to supply the information of the finite element (FE) modeling such as: elementary and global matrices, boundary condition, geometric properties, coordinate systems, etc. In addition, to solve the resulting equations of the aeroviscoelastic system, an adapted version of the PK method is proposed together with the using of Roger's approximation to calculate the generalized aerodynamic matrix (GAM) and estimate the critical flutter speed for curved sandwich panels using materials viscoelastic. Further, is studied the influence of parameters that characterize the performance of the viscoelastic treatment, such as temperature and layer thickness.